Modern approaches for modelling dystonia and Huntington's disease in vitro and in vivo - Zhunina, Olga A. (Int J Exp Pathol, 2019)
Dystonia associated with Huntington's disease, Parkinson's disease or other neurodegenerative diseases substantially affects patients’ quality of life and is a major health problem worldwide. The above‐mentioned diseases are characterized by neurodegeneration accompanied by motor and cognitive impairment and often have complex aetiology. A frequent feature of these conditions is the abnormal accumulation of protein aggregates within specific neuronal populations in the affected brain regions. Familial neurodegenerative diseases are associated with a number of genetic mutations. Identification of these mutations allowed creation of modern model systems for studying neurodegeneration, either in cultured cells or in model animals. Animal models, especially mouse models, have contributed considerably to improving our understanding of the pathophysiology of neurodegenerative diseases. These models have allowed study of the pathogenic mechanisms and development of new disease‐modifying strategies and therapeutic approaches. However, due to the complex nature of these pathologies and the irreversible damage that they cause to the neural tissue, effective therapies against neurodegeneration remain to be elaborated. In this review, we provide an overview of cellular and animal models developed for studying neurodegenerative diseases, including Huntington's disease and dystonia of different origins.